TRPM8 Activation via 3-Iodothyronamine Blunts VEGF-Induced Transactivation of TRPV1 in Human Uveal Melanoma Cells - Walcher, Lia; Budde, Clara; Böhm, Arina; Reinach, Peter S.; Dhandapani, Priyavathi; Ljubojevic, Nina; Schweiger, Markus W.; von der Waydbrink, Henriette; Reimers, Ilka; Köhrle, Josef; Mergler, Stefan (Frontiers in Pharmacology, 2018)
In human uveal melanoma (UM), tumor enlargement is associated with increases in aqueous humour vascular endothelial growth factor-A (VEGF-A) content that induce neovascularization. 3-Iodothyronamine (3-T1AM), an endogenous thyroid hormone metabolite, activates TRP melastatin 8 (TRPM8), which blunts TRPV1 activation by capsaicin (CAP) in human corneal, conjunctival epithelial cells and stromal cells. We compare here the effects of TRPM8 activation on VEGF-induced transactivation of TRPV1 in an UM cell line (92.1) with those in normal primary porcine melanocytes (PM) since TRPM8 is upregulated in melanoma. Fluorescence Ca2+-imaging and planar patch-clamping characterized functional channel activities. CAP (20 µM) induced Ca2+ transients and increased whole-cell currents in both the UM cell line and PM whereas TRPM8 agonists, 100 µM menthol and 20 µM icilin, blunted such responses in the UM cells. VEGF (10 ng/ml) elicited Ca2+ transients and augmented whole-cell currents, which were blocked by capsazepine (CPZ; 20 µM) but not by a highly selective TRPM8 blocker, AMTB (20 µM). The VEGF-induced current increases were not augmented by CAP. Both 3-T1AM (1 µM) and menthol (100 µM) increased the whole-cell currents, whereas 20 µM AMTB blocked them. 3-T1AM exposure suppressed both VEGF-induced Ca2+ transients and increases in underlying whole-cell currents. Taken together, functional TRPM8 upregulation in UM 92.1 cells suggests that TRPM8 is a potential drug target for suppressing VEGF induced increases in neovascularization and UM tumor growth since TRPM8 activation blocked VEGF transactivation of TRPV1.